Kunst lebt ! : Die Welt mit anderen Augen sehen. - Brune, Thomas; Buderer, Hans-Jürgen; Fritz, Nicole; Heermann, Ingrid; Holsten, Siegmar; Inboden, Gudrun; Joly, Jean-Baptiste; Kosche, Thomas; Michel, Thomas; Osterwold, Tilman; Pfarr, Ulrich; Schmidt, Annette; et al. (Stuttgart : Ministerium für Wissenschaft, Forschung und Kunst Baden-Württemberg Stuttgart Snoeck Verlagsgesellschaft mbh Köln, 2006)
Ackermann, Max ; Baselitz, Georg ; Beuys, Joseph ; Birchler, Alexander ; Buetti, Daniele ; Dijkstra, Rineke ; Dumas, Marlene ; Dürer, Albrecht ; Fischer, Roland ; Fleury, Sylvie ; Fujihata Masaki ; Gehry, Frank O. ; Gertsch, Franz ; Gröting, Asta ; Gursky, Andreas ; Hastenteufel, Sandra ; Höfer, Candida ; Honert, Martin ; Hubbard, Teresa ; Huber, Thomas ; Jawlensky, Alexej von ; Knoebel, Imi ; Longo, Robert ; Morley, Malcolm ; Mullican, Matt ; Nauman, Bruce ; Palermo, Blinky ; Peyton, Elisabeth ; Poirier, Anne & Patrick ; Polke, Sigmar ; Rehberger, Tobias ; Richter, Gerhard ; Rondinone, Ugo ; Rosenbach, Ulrike ; Roth, Dieter ; Ruff, Thomas ; Schmidt-Rasmussen, Christian ; Schulze, Andreas ; Schütte, Thomas ; Sumell, Jackie ; Taut, Bruno ; Zittel, Andrea ; Zobernig, Heimo
Duits
boek